2020
DOI: 10.3390/rs12213604
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Daytime and Nighttime Warming in Typical Climatic Zones along the Eastern Coast of China and Its Influence on Vegetation Activities

Abstract: In this dissertation, the author adopted the normalized difference vegetation index (NDVI) and meteorological data from 1982 to 2016 of the typical climate zones in coastal areas of China to analyze the influence of daytime and nighttime warming asymmetric changes in different seasons on vegetation activities during the growing season period according to the copula function theory optimized based on Markov chain Monte Carlo (MCMC). The main conclusions are as follows: (1) The seasonal daytime and nighttime war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
0
1
0
Order By: Relevance
“…Historical data from 2001 to 2020 show an increase in grassland areas and an upward trend in NDVI in the Tibetan Plateau, which may have partially obscured the response of NDVI to moisture changes [38]. In Guangdong province, earlier studies have identified temperature as a primary factor affecting vegetation growth [39,40]. The saturation effect in NDVI may have contributed to the high positive correlation observed between NDVI and SPEI3.…”
Section: Vegetation Indices Response To Water Stressmentioning
confidence: 99%
“…Historical data from 2001 to 2020 show an increase in grassland areas and an upward trend in NDVI in the Tibetan Plateau, which may have partially obscured the response of NDVI to moisture changes [38]. In Guangdong province, earlier studies have identified temperature as a primary factor affecting vegetation growth [39,40]. The saturation effect in NDVI may have contributed to the high positive correlation observed between NDVI and SPEI3.…”
Section: Vegetation Indices Response To Water Stressmentioning
confidence: 99%
“…Asymmetric diurnal warming is one of the main features of global warming. In the past 35 years, the trend of daytime and nighttime warming in Jiangsu province is obvious, and the rate of daytime and nighttime warming is asymmetric [7]. The rate of increase in global warming in the daytime was lower than that at night, this asymmetric warming is likely to intensify in the coming decades, ultimately leading to a drop in the day and night temperature range [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The variations in DTR have significant impact on the growth and development of vegetation [10]. As a crucial factor in the vegetation ecosystem, the DTR affects the growth dynamics, structures, and functions of vegetation by altering its growth environments [11]. Based on long-term remote sensing data and meteorological data, previous studies have explored the spatiotemporal distribution characteristics of NDVI and its relationship with precipitation and temperature at various time scales [12][13][14].…”
Section: Introductionmentioning
confidence: 99%